Stand characteristics and temperature’s effect on bilberry availability and quality - Chaimungkhun Johansson, Jennifer (2022)
Stand characteristics is a crude description of a forest and provides general knowledge of what the forest looks like, for example plant composition and site productivity. Factors and measurements like tree canopy and basal area affects the near ground microclimate through temperature regulation, light intake, and available soil nutrient. This study focuses on the effect of stand characteristics and temperature on availability and quality of the ericaceous dwarf shrub bilberry, Vaccinium myrtillus. The data used derives from central Södermanland, Sweden, and has been collected during a short time-period of two weeks by the end of March this year, 2021. The temperature loggers were installed the previous year and retrieved this year. Day temperature decreased with increased basal area while the night temperature was affected by maturity classes. There was a significant difference between bilberry coverage and maturity classes. A further pairwise comparison revealed the difference to be between final harvest and the other maturity classes. However, when looking at bilberry weight, it was only positively correlated to bilberry coverage. The quality of the dwarf shrub as forage, defined as Total Digestible Nutrients, was affected by neither maturity classes nor the weight. By connecting bilberry to suitable silviculture practise and longer rotation periods may increase the availability and thus mitigating ungulate related forest damages.